The mediating effect of technology in teaching and learning in the relationship between teacher readiness in ICT integration and cognitive performance - Jr. S. Cavan, Wilfredo (Eximia, 2021)
This research aims to know the mediating effect of technology in teaching and learning in the relationship between teacher readiness in ICT integration and cognitive performance to the 400 teacher respondents teaching Filipino in the province and in the Division of Davao del Sur. The technology in teaching and learning is the mediating variable in the study in the relationship between teacher readiness in ICT integration and cognitive performance. This study used non-experimental quantitative design and used descriptive correlation to gather data, ideas, evidence and information. The researcher used google forms to gather relevant data in this study. The adapted questionnaire was used as instrument as variables in this study, technology in teaching and learning, teacher readiness in ICT integration, and cognitive performance. The questionnaire was then evaluated and assessed by the experts. Based on the objectives of this study using mean, the result showed that there is a high level of teacher readiness in ICT integration, cognitive performance at technology in teaching and learning. Using Pearson-r, the result showed that there is a significant relationship between technology in teaching and learning to the teacher readiness in ICT integration, also there is a significant relationship between technology in teaching and learning and cognitive performance and lastly there is a significant relationship between teacher readiness in ICT integration and cognitive performance. Furthermore, using medgraph Sobel z-test, the result of the study showed that there is a partial mediation in the effect of technology in teaching and learning in the relationship between teacher readiness in ICT integration and cognitive performance.